The legal regime of the letter of bank guarantee According to jurisprudential theories and comparative legislation - mohamed zakaria, Chikh (International Journal of Psychosocial Rehabilitation, 2022)
Bank letters of guarantee are considered one of the most important banking activities carried out by banks in the field of economic activity, since they represent an alternative to monetary insurance to ensure the proper fulfillment of obligations arising between contracting parties on the one hand, in addition to granting them multiple advantages to all parties, whether for the ordering client requesting the issuance, or the beneficiary of the letter, or the bank at the origin of the letter. Given the importance of this international banking service, the International Chamber of Commerce has made great efforts to develop unified rules to regulate the legalization of the use of letters of guarantee worldwide in a single format given the many problematic legislation that raised the subject of the bank letter of guarantee, In particular, as regards its legal adaptation, from which the Jurisprudence has departed in order to determine it, Which I will try to analyze in this article.